Streptococcus pluranimalium 2N12 Exerts an Antagonistic Effect Against the Swine Pathogen Actinobacillus pleuropneumoniae by Producing Hydrogen Peroxide - Vaillancourt, Katy; Frenette, Michel; Gottschalk, Marcelo; Grenier, Daniel (Frontiers in Veterinary Science, 2021)
Actinobacillus pleuropneumoniae is the causal agent of porcine pleuropneumonia, a highly contagious and often deadly respiratory disease that causes major economic losses in the swine industry worldwide. The aim of the present study was to investigate the hydrogen peroxide (H2O2)-dependent antagonistic activity of Streptococcus pluranimalium 2N12 (pig nasal isolate) against A. pleuropneumoniae. A fluorimetric assay showed that S. pluranimalium produces H2O2 dose- and time-dependently. The production of H2O2 increased in the presence of exogenous lactate, suggesting the involvement of lactate oxidase. All twenty strains of A. pleuropneumoniae tested, belonging to eighteen different serovars, were susceptible to H2O2, with minimal inhibitory concentrations and minimal bactericidal concentrations ranging from 0.57 to 2.3 mM. H2O2, as well as a culture supernatant of S. pluranimalium, killed planktonic cells of A. pleuropneumoniae. Treating the culture supernatant with catalase abolished its bactericidal property. H2O2 was also active against a pre-formed biofilm-like structure of A. pleuropneumoniae albeit to a lesser extent. A checkerboard assay was used to show that there were antibacterial synergistic interactions between H2O2 and conventional antibiotics, more particularly ceftiofur. Based on our results and within the limitations of this in vitro study, the production of H2O2 by S. pluranimalium could be regarded as a potential protective mechanism of the upper respiratory tract against H2O2-sensitive pathogens such as A. pleuropneumoniae.